Economic and Legal Issues for Training Reserve Personnel Among the University Students in Kazakhstan and Foreign Countries - RYSKULBEKOV, Aydin I.; BURNAYEV, Zufar R.; VAFIN, Kharis Sh.; KOZHANULY, Manasbay; BORASHEV, Askar K. (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020, 2020)
In modern conditions, at the stage of professionalization of the Armed Forces of Kazakhstan, it is necessary to reorient to own forces, to concentrate the intellectual and financial potential on the further development of the domestic system of military education and military science. The aim of this study is to consider the development trends of the training of reserve officers and military personnel in different countries, as well as highlight on the basis of the obtained data the main effective ways to improve the qualifications and improve military-patriotic education of military personnel. As a result, stages of the implementation of ways to improve the military-patriotic education of student youth are proposed, and it also presents what development prospects this brings in terms of improving the Kazakh army, as well as open opportunities for improving the teaching of military training in higher educational institutions.